Influencing Negotiation Willingness in the Middle East: The Potential Contributions of Private Actors. Issue 2 (April 2016) - Hofmann, Claudia; Goerzig, Carolin
Abstract : Numerous efforts to solve the Israeli–Palestinian conflict through diplomacy have taken place over the last four decades. To shed light on this dilemma in this article, the role that private actors and nongovernmental organizations (NGOs) can play to enhance the negotiation willingness of nonstate armed groups was examined. It was argued that the NGOs in particular could play key roles in promoting the negotiation willingness of nonstate actors and also in influencing their internal dynamics and increasing their cohesion. Specifically, we examine two pairs of efforts to resolve the conflict in Israel and Palestine: the "Road Map" and the track two Geneva Initiative of 2003, and the Olmert Peace Plan and Jimmy Carter's visit to the Middle East in 2008. In the first pair, NGO efforts yielded unexpected results. The Palestinians were ready to compromise even though the deal offered by the Israelis did not seem very generous. In the second pair, the reaction of the Palestinians to Israeli Prime Minister Ehud Olmert's generous peace offer seemed especially puzzling, illustrating, the internal dynamics between the Palestinian factions. Negotiation willingness was closely related to cohesion, and that cohesion plays an important role in conflict negotiations. President Jimmy Carter's efforts in 2008 to enhance cohesion among the Palestinians illustrated the potential that NGOs have to complement official negotiations.